Strains in Sustainability Debates: Traditional Ecological Knowledge and Western Science through the Lens of Extension Agents in a Pastoral Region - Easdale, Marcos Horacio; Perez Leon, Natalia; Aguiar, Martín Roberto (Wiley Online Library, 2020)
Those involved in sustainability debates on developmental pathways concur in the synergistic potential of integrating traditional ecological knowledge (TEK) and Western scientific approaches. Transhumant pastoralism is a livelihood strategy adapted to spatiotemporal environmental variability in many mountainous and arid regions worldwide. This form of livelihood is based on a mobile logic that is increasingly threatened by novel lifestyles promoted from a Western mind-set and by climate change. The aim of this article is to identify and characterize the different perspectives of environmental and social issues in a pastoral region and their association with labor collaboration among extension agents, framed in an institutional action. We tackled the inquiry about viewpoints with Q methodology and related it to regional problems, alternative solutions, and future development pathways for transhumant pastoralism and landscape management in northwest Patagonia. We identified six perspectives and characterized them with their topological position in the social network. Mediating positions registered the highest network centrality of labor collaborations among agents, whereas more dominant perspectives emphasizing TEK or scientific knowledge registered intermediate centrality. There was consensus on the need for sustainable developmental options, but the emphasis on combining knowledge still needs convergent solutions.